Computed Tomography Measurements of Paranasal Sinus at a Tertiary Care Center of Nepal - Paudel, Bigyan; Chaulagain, Rajib; Bhusal, Gehendra (Journal of Karnali Academy of Health Sciences, 2022)
Background: Paranasal sinus is an anatomical structure located in head and facial bones. The proximity of the sinus with vital structures make them a very important. Variations in paranasal sinus has been suggested in literature. The present study was aimed to estimate the different measurements of paranasal sinus at a tertiary care center of Nepal.Methods: A descriptive cross-sectional study was conducted at the Chitwan Medical College from January 2021 to July 2021. One hundred eight patients fulfilling the inclusion criteria participated in this study. Computed tomography scans were performed using Siemens 128 slice Somatom Definition Edge CT scan machine. The measurement of maxillary sinuses and its volume, the measurement of frontal sinus and sphenoidal sinus was done. All the data were entered into Microsoft Excel 2019 and then transferred to Statistical Package for Social Sciences version 21 for analysis. The data was analyzed using presented as frequency, percentages, mean and standard deviation Results: In total 108 patients (72 (66.7%) males and 36 (33.3%) females) participated in this study. The mean age of patients was 40.74±17.93 years. The volume of maxillary sinus in male was greater in the left side (18.68±1.34 cm3) than the right side (17.66±2.21cm3)). Whereas the volume in both right and left side of female maxillary sinus was similar. The anteroposterior diameter of the frontal sinus was greater on the left side of male (1.01±1.42 cm) than in the female (0.81±0.42 cm). Fourteen participants had unilateral non-pneumatized frontal sinus while 13 had bilateral non-pneumatized frontal sinus.Conclusion: The volume of maxillary sinus was higher in male than in female suggesting that variation do exists in our region too. This study also observed the difference in the measurement of frontal sinus in the same individual.